Causes and consequences of centrosome abnormalities in cancer - Godinho, S. A. (The Royal Society, 2014)
Centrosome amplification is a hallmark of cancer. However, despite significant progress in recent years, we are still far from understanding how centrosome amplification affects tumorigenesis. Boveri's hypothesis formulated more than 100 years ago was that aneuploidy induced by centrosome amplification promoted tumorigenesis. Although the hypothesis remains appealing 100 years later, it is also clear that the role of centrosome amplification in cancer is more complex than initially thought. Here, we review how centrosome abnormalities are generated in cancer and the mechanisms cells employ to adapt to centrosome amplification, in particular centrosome clustering. We discuss the different mechanisms by which centrosome amplification could contribute to tumour progression and the new advances in the development of therapies that target cells with extra centrosomes.